UN Security Council actions against terrorism and the legal nature of the sanctions - Muikku, Minna (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis examines the measures of the United Nations Security Council in combating terrorism and the character of these actions. The topic of the thesis is closely linked with the resolutions made by the Security Council and the resolution 1373 has a specific significance in this research. The resolution 1373 was established after the attacks of 11th September 2001 and it has been widely regarded as an act of supra-national legislation. The Security Council has a responsibility for maintaining international peace and security according to the article 24 of the United Nations Charter. The Chapter VII of the Charter includes the main parts of the security system because it gives the Security Council enforcement powers and a mandate to make binding decisions on states. The goal of the research is to find out, why do the resolution 1373 and the actions after that raise critique in the light of the jurisdictions. In addition, the goal is to answer to a question, why and from which reasons have the jurisdictional powers been exceeded. The research is mainly using a legal dogmatic as a method of the study. In addition, qualitative research method and induction are used in the research. The most important sources from the literature are the books from Amnéus, Diana – Svanberg – Torpman, Katinka (eds.) (Peace and Security. Current Challenges in International Law) and from Lehto, Marja (International Responsibility for Terrorist Acts. A Shift Towards More Indirect Forms of Responsibility). The central findings of the research are that in some cases, the Security Council has taken a role of a legislative authority and gone beyond its limits. However, the role of the Security Council in maintaining peace and security is important and the states need the guidance of the Security Council.